Relativity, gravitation, and cosmology : a basic introduction - Cheng, Ta-Pei (Oxford master series in physics ;, 2005)
This book is an introduction to Einstein's general theory of relativity, suitable for advanced undergraduate or beginning graduate courses. The content is structured so that interesting applications, such as gravitational lensing, black holes and cosmology, can be presented without the readers having to first learn the difficult mathematics of tensor calculus. The mathematical accessibility and the presentation of the book make it practical for readers to study the subject on their. own. - ;Einstein's general theory of relativity is introduced in this advanced undergraduate and beginning gradu.